Effect of 3D-Printed Models on Cadaveric Dissection in Temporal Bone Training. Issue 4 (December 2021) - Frithioff, Andreas; Frendø, Martin; Weiss, Kenneth; Foghsgaard, Søren; Pedersen, David Bue; Sørensen, Mads Sølvsten; Wuyts Andersen, Steven Arild
Objective: Mastoidectomy is a cornerstone in the surgical management of middle and inner ear diseases. Unfortunately, training is challenged by insufficient access to human cadavers. Three-dimensional (3D) printing of temporal bones could alleviate this problem, but evidence on their educational effectiveness is lacking. It is largely unknown whether training on 3D-printed temporal bones improves mastoidectomy performance, including on cadavers, and how this training compares with virtual reality (VR) simulation. To address this knowledge gap, this study investigated whether training on 3D-printed temporal bones improves cadaveric dissection performance, and it compared this training with the already-established VR simulation. Study Design: Prospective cohort study of an educational intervention. Setting: Tertiary university hospital, cadaver dissection laboratory, and simulation center in Copenhagen, Denmark. Methods: Eighteen otorhinolaryngology residents (intervention) attending the national temporal bone dissection course received 3 hours of mastoidectomy training on 3D-printed temporal bones. Posttraining cadaver mastoidectomy performances were rated by 3 experts using a validated assessment tool and compared with those of 66 previous course participants (control) who had received time-equivalent VR training prior to dissection. Results: The intervention cohort outperformed the controls during cadaver dissection by 29% ( P < .001); their performances were largely similar across training modalities but remained at a modest level (~50% of the maximum score). Conclusion: Mastoidectomy skills improved from training on 3D-printed temporal bone and seemingly more so than on time-equivalent VR simulation. Importantly, these skills transferred to cadaveric dissection. Training on 3D-printed temporal bones can effectively supplement cadaver training when learning mastoidectomy.